The Drosophila maternal effect locus deadhead encodes a thioredoxin homolog required for female meiosis and early embryonic development. - Salz, H.K.; Flickinger, T.W.; Mittendorf, E.; Pellicena-Palle, A.; Petschek, J.P.; Albrecht, E.B. (Genetics, 1994)
This study describes the identification, function and molecular characterization of deadhead, a Drosophila thioredoxin homolog. Although in vitro studies have shown that thioredoxin can post-translationally regulate the activity of many different proteins, we find that this homolog is not essential for viability. The phenotypic analysis of two different mutations which eliminate function suggests that dhd is essential for female meiosis. The majority of eggs laid by females homozygous for null mutations are fertilized but fail to complete meiosis. A small number of escaper embryos initiate development and display a range of phenotypes suggesting functions in both preblastoderm mitosis and head development. Our analysis of deadhead's RNA expression pattern is consistent with its maternal effect function: the RNA is predominately expressed in the nurse cells of the ovary, is maternally deposited into the egg, but does not appear to be zygotically expressed during embryogenesis. Thus both our genetic and molecular data are consistent with a function during meiosis and preblastoderm mitosis. Whether the head defect indicates an additional function or is an indirect consequence of earlier defects remains to be determined.